It's Not Me, It's You: The Disconnect of Physical Education Teachers to Physical Activity in the Gym - Dean Culpepper; Lorraine Killion (MDPI AG, 2015)
American adults and an increasing number of children, are not meeting the recommended amounts of daily physical activity. Research has documented the effects of low activity on health and increasingly new research has shown that low activity levels now impact academic achievement. Physical education (PE) can play an important role if the children participating are obtaining enough physical activity while in class and the PE program has not been targeted with cutbacks. The purpose of this study was to identify the amount and intensity of activity in PE classes. The results indicate that on average students at all levels are not meeting the activity requirements. In addition, PE teachers' perceptions of physical activity in their own class does not match actual activity levels. PE teachers must do a better job of increasing activity levels in their classrooms. Mounting research indicates students perform better academically if they are physically active. PE is the only subject where teachers can organize activities that meet both activity and intensity requirements.